Legal Aspects of Maternity Nursesperforming Childbirth Assistance Measures in the Framework of Carrying Out Doctor’s Duties Against the Birth Process in Breach Locations - Makhfudli; Gregory Agung Himawan; Nisa AmaliyaVariansyah; MokhamadKhoirul Huda (Indian Journal of Forensic Medicine & Toxicology, 2022)
Health is a human right, meaning that everyone has the same rights in obtaining access to healthservices and professionalism from health workers. Nurses are the most numerous health workers inIndonesia. Nursing staff who perform nursing actions must be following the competence of nurses andLaw Number 38 of 2014 concerning Nursing. The purpose of writing this article is to find out how thelegal aspects of maternity nurses who carry out delivery assistance actions carry out the doctor’s dutiesin the Breach delivery process By using the normative juridical research method, it can be concludedthat the competence of the maternity nurse is to assist childbirth but does not have the authority toprovide delivery assistance, especially in cases with fatal risks that can cause death to the mother andfetus. When referring to the criminal provisions of Law Number 36 of 2009 concerning Health Workers,Article 84 paragraph (1), any Health Worker who commits serious negligence resulting in serious injuryto the Health Service Recipient shall be sentenced to a maximum imprisonment of 3 (three) years. Thenin paragraph (2), namely If the gross negligence as referred to in paragraph (1) results in death, eachHealth Worker shall be sentenced to a maximum imprisonment of 5 (five) years.